Transformasi Pembelajaran PAI Melalui Integrasi PPKS Untuk Menciptakan Karakter dan Literasi Agama Siswa SLTP di Kabupaten Pandeglang - Hamdanah, Hamdanah; Rahmi Fauziah, Dewi; Romdona, Dede; Munawir, Amin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The research highlights the cultural challenges in Pandeglang, particularly in enhancing character education and child protection. The increasing cases of sexual violence against adolescents in schools and the traditional, normative nature of PAI learning, which lacks contextual relevance to students' real-life issues, underline the necessity of this research. By integrating PPKS into PAI learning, this study proposes a strategic, innovative approach to teaching not only spiritual values and worship but also critical awareness of self-protection and understanding boundaries in social interactions. Purpose: This study aims to explore the integration of the Sexual Violence Prevention Service Unit (PPKS) into Islamic Religious Education (PAI) to strengthen character building and religious literacy among junior high school students in Pandeglang Regency. Method: The research uses a mixed-methods approach with an Explanatory Sequential Design, combining quantitative data from surveys with qualitative insights from interviews and observations. Result: The findings indicate that the integration of PPKS significantly improves students’ character and religious literacy, contributing to a holistic approach in Islamic education. Conclusion: The study emphasizes the need for a curriculum responsive to contemporary social issues and recommends PPKS integration as a strategic solution for character education in junior high schools, especially in areas facing similar social challenges. Implication: Further research is suggested to use a longitudinal approach and incorporate AI-based learning analytics to refine the model’s application across diverse cultural contexts.